Answer:
x = 2
y = 1
Step-by-step explanation:
3x - y = 5..............(1)× 1
2x + y = 5...….......(2)× 1
3x - y = 5..............(3)
2x + y = 5.............(4)
Cancel y
3x + 2x = 5 + 5
5x = 10
Divide both sides by 5
x = 2
Substitute for the value of y
3x - y = 5
3(2) - y = 5
6 - y = 5
6 - 5 = y
1 = y
y = 1
Answer:
x=14
Step-by-step explanation:
you should set up your problem like this:
5x=3x+28
use order of operations aka PEMDAS to solve
you're answer is 14
The axis of symmetry is at x = -3.
This can be found by looking at the basic form of vertex form:
y = (x - h)^2 + k
In this basic form the vertex is (h, k). By looking at what is plugged into the equation, it is clear that h = -3 and k = -4. This means the vertex is at (-3, -4).
It is a fact that the axis of symmetry is a vertical line of x = (vertex value of x). So we can determine that the axis of symmetry is at x = -3